Enzymatic synthesis of supported CdS quantum dot/reduced graphene oxide photocatalysts. Issue 15 (14th May 2019) - Spangler, Leah C.; Cline, Joseph P.; Sakizadeh, John D.; Kiely, Christopher J.; McIntosh, Steven
Abstract : Biomineralization provides a route towards scalable, aqueous phase synthesis of heterostructured photocatalysts for solar driven hydrogen production. Abstract : Photocatalysis is an attractive, sustainable, and potentially low-cost route to capture solar energy as fuel. However, current photocatalytic materials synthesis routes are not easily scaled-up to the magnitude required to impact our energy consumption due to both economic and environmental concerns. While the elements utilized are often earth abundant, typical synthetic routes utilize organic solvents at elevated temperatures with relatively expensive precursors. Herein, we demonstrate the fully biomineralized synthesis of a quantum confined CdS/reduced graphene oxide (CdS/rGO) photocatalyst catalyzed by the single enzyme cystathionine γ-lyase (CSE). The synthesis is performed at pH 9 in a buffered aqueous solution, under ambient conditions, and utilizes the low-cost precursors Cd acetate, l -cysteine, graphene oxide, and a poly-l -lysine linker molecule. CSE actively decomposesl -cysteine to generate reactive HS − in aqueous solution at pH 9. Careful selection and control of the synthesis conditions enable both reduction of graphene oxide to rGO, and control over the mean CdS nanocrystal size. The CdS is conjugated to the rGO via a poly-l -lysine crosslinker molecule introduced during rGO formation. The completed CdS/rGO photocatalyst is capable of producing H2, without the aid of a noble metal co-catalyst, at a rate of 550 μmol h −1 g −1 for an optimized CdS/rGO ratio. This rate is double that measured for unsupported CdS and is comparable to CdS/rGO photocatalysts produced using more typical chemical synthesis routes. Single enzyme biomineralization by CSE can produce a range of metal chalcogenides without altering the enzyme or benign approach, making this an easily adaptable procedure for the sustainable production of a wide variety of important photocatalyst systems.